Expert System for Nutrition Managemen - Rogério Belai, Demitrius; Pedreira Silva, Patrick; da Silva, Elvio Gilberto; Pavarini da Luz, Larissa (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2016)
The good nutrition helps for a healthy life. The nutriocionist is the professional responsible for maintaining the eating habits. This paper aims to develop a software that will help the nutritionist in assembling a weekly menu using production rules, breadth-first search and linear programming. Linear programming is used for calculating the amounts in dishes, the breadth-first search in combination and the production rules in the selection of dishes and validation of menus. The software presented is capable of generating valid menus, compatible with the basic daily needs.